Greece : Request for Extended Arrangement Under the Extended Fund Facility: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report, 2012)
This paper presents the staff report for Greece's request for an Extended Arrangement under the Extended Fund Facility. The Greek economy fell into deep twin structural deficits after euro adoption. Easy access to financing at low interest rates fuelled rapid borrowing by the private and public sectors. Between euro accession in 2001 and 2009, private sector credit almost doubled in percent of GDP, financed mainly through the domestic banking system. Massive sovereign borrowing from international bond markets pushed government debt from 100 percent of GDP to about 130 percent of GDP during this timeframe.